Effects of peripheral and nonperipheral substitution to the spectroscopic, electrochemical and spectroelectrochemical properties of metallophthalocyanines - Arican, Duygu; Arici, Mursel; Ugur, Ahmet Lutfi; Erdogmus, Ali; Koca, Atif (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The syntheses, spectroscopic and electrochemical properties of metallo-phthalocyanine complexes, tetra- and octa-substituted with 3,4-(dimethoxyphenylthio) moieties at non-peripheral and peripheral positions were studied. These complexes were characterized by FT-IR, mass spectroscopy, electronic spectroscopy and electrochemical methods. 3,4-(Dimethoxyphenylthio) moieties increase the solubility of the complexes in various polar and nonpolar organic solvents and prevent the aggregation (in the same solvents) within a wide concentration range. Electronic absorption spectroscopy revealed that the presence of electron donating sulphur on synthesized complexes shift the Q-band of the complexes to the higher wavelengths. Redox active metal centers, Co-II, Fe-II and (MnOAc)-O-III into the phthalocyanine core extend the redox worthy of the complexes due to the reversible metal-based reduction and oxidation couples of the metal centers. In situ electrocolorimetric measurements of the complexes allow quantification of color coordinates of each electrogenerated anionic and cationic redox species. Electrochemical and in situ spectroelectrochemical analysis indicate that cobalt and manganese phthalocyanines catalyze the molecular oxygen in aprotic media. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thiol-substituted metallophthalocyanines; Electrochemistry; Spectroelectrochemistry; Oxygen reduction reaction; Chronocolorimetry; METAL-FREE; IN-SITU; FUNCTIONAL PHTHALOCYANINES; ELECTROCATALYTIC OXIDATION; ZINC PHTHALOCYANINES; OXYGEN REDUCTION; COBALT; MANGANESE; IRON; COMPLEXES